Super Kutler flap: an alternative technique for reconstruction of fingertip defects. (July 2017) - Arpaci, E.; Unlu, R. E.; Altun, S.; Ertas, N. M.
The bilateral V-Y flap concept for fingertip reconstruction was first desribed by Kutler. This method has limitations, such as flap size and advancement, therefore larger flap modifications are described to increase the advancement capacity of the flaps. We described a small direct-flow homodigital island flap method, called the 'super Kutler flap', for recontruction of finger pulp defects. In addition, neurorrhaphy was performed between the cut ends of the digital nerves to prevent neuroma formation. This method was used in 10 fingers in patients who had undergone pulp tissue reconstruction of fingertip defects from May 2008 to October 2011. The mean defect size was 2.2 × 1.7 cm. The mean static two-point discrimination was 3.5 mm and the mean Semmes–Weinstein monofilament test of the flaps was 2.83 g. The super Kutler flap provides an altenative option for reconstruction of fingertip defects. Level of evidence: IV